Telescopic synthesis of cellulose nanofibrils with a stable dispersion of Fe(0) nanoparticles for synergistic removal of 5-fluorouracil - Sajab M.S.; Mohan D.; Santanaraj J.; Chia C.H.; Kaco H.; Harun S.; Kamarudin N.H.N. (Nature Publishing Group, 2024)
Indexed by WOS/SCOPUS/ERA